2013
DOI: 10.1115/1.4025781
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of GaN Growth in a Metalorganic Chemical Vapor Deposition Process

Abstract: A detailed mathematical model for the growth of gallium nitride in a vertical impinging metalorganic chemical vapor deposition (MOCVD) reactor is developed first, and the complete chemical mechanisms are introduced. Then, one validation study is conducted to ensure its accuracy. After that, the flow, temperature and concentration profiles are predicted by numerical modeling. The dependence of the growth rate and uniformity of the deposited layers on operating conditions, such as reactor operating pressure, sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Figure h shows the flow chart of NR growth, which involves three major steps: (1) The pit is first filled by GaN nuclei, and followed by NR growth axially (c-axis) proportional to the radial growth. The conformation of the NR growth axially in proportion with the radial growth in the initial NR growth is consistent with previous reports. , This is labeled as Stage 1 in blue on Figure f,g. (2) We neglect the migration length of N adatoms during the NR growth because of the high evaporation rate of N atoms. , The migration and nucleation barrier of Ga adatoms are considerably high on m-plane sidewalls of GaN NRs, which contributes to the shorter migration length of Ga adatoms on sidewalls. , To prove the previous statement, we fabricated a sample with lower V/III and observed that no Ga droplet exists on the sidewall of the NR (see Figure S13).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figure h shows the flow chart of NR growth, which involves three major steps: (1) The pit is first filled by GaN nuclei, and followed by NR growth axially (c-axis) proportional to the radial growth. The conformation of the NR growth axially in proportion with the radial growth in the initial NR growth is consistent with previous reports. , This is labeled as Stage 1 in blue on Figure f,g. (2) We neglect the migration length of N adatoms during the NR growth because of the high evaporation rate of N atoms. , The migration and nucleation barrier of Ga adatoms are considerably high on m-plane sidewalls of GaN NRs, which contributes to the shorter migration length of Ga adatoms on sidewalls. , To prove the previous statement, we fabricated a sample with lower V/III and observed that no Ga droplet exists on the sidewall of the NR (see Figure S13).…”
Section: Resultssupporting
confidence: 91%
“…The conformation of the NR growth axially in proportion with the radial growth in the initial NR growth is consistent with previous reports. 35,36 This is labeled as Stage 1 in blue on Figure 4f,g. ( 2) We neglect the migration length of N adatoms during the NR growth because of the high evaporation rate of N atoms.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…8 for Silicon deposition for model validation. Deposition of several other materials like TiN, SiC, GaN and GaAs have been investigated for a range of applications in electronic and optical systems [18]. Thus, this brief discussion, along with the examples, illustrate the approach for modelling such multiscale problems, which involve both micro-and macroscale mechanisms in the system.…”
Section: Multiple Scales Within the Flowmentioning
confidence: 99%
“…The design and the optimization of the MOCVD process [39] is a challenge that needs to be tackled for the commercial development of GaN based devices. Numerical modeling of the MOCVD process for the deposition of GaN films in two dimensions [39][40][41][42][43] and three dimensions [44][45][46] has been performed. Meng and Jaluria [47] modeled a 3D vertical rotatingdisk reactor for the deposition of GaN.…”
Section: Introductionmentioning
confidence: 99%